CREATIVE DEVELOPMENT OF OLDER PRESCHOOLERS AND PRIMARY SCHOOL STUDENTS AT ART AND CRAFT CLASSES IN INSTITUTIONS OF NON-FORMAL EDUCATION - Dykhta-Kirff, Viktoriia; Kornienko, Anna (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article deals with the analysis of theoretical generalizations and the current state of the practice of creative development of older pre-schoolers and primary school students. The purpose of the article is to reveal the content and methods of creative development of older preschoolers and primary school students in art and craft classes in institutions of non-formal education. The specified goal determined the setting of the following tasks: to carry out a methodological description of the educational program for creative development of older preschoolers and primary school students based on general pedagogical principles of creating age-related content; to determine the prospects for further research on the problem. To solve the problems, the following methods were used: general research methods (analysis, synthesis, systematization, classification, comparison, generalization), content analysis of the educational program and expected results of the educational process. The analysis of theoretical sources and the current educational practice of the formation of 5-7 years old students’ creativity made it possible to identify contradictions between: the objective need of society for education of a creative personality and the insufficient degree of solving the relevant issues in the educational environment; the necessity to develop older preschoolers and primary school students’ creativity and the imperfection of the theoretical and methodological foundations for solving this problem; the high potential that child development centres have for the formation of older preschoolers and primary school students’ creativity and the lack of appropriate scientific and methodological support. The article describes the educational program and techniques of creative development of older preschoolers and primary school students in art and craft classes in institutions of non-formal education. The educational program consists of four blocks based on a systemic approach: “Development of Imaginative Thinking”; “Development of Logical Thinking”; “Development of Fine Motor Skills”; “Development of Imagination and Memory”. The conclusions emphasize that implementing the authors’ technique of creative development of preschoolers and primary school students has become a factor in creative development, emotional receptivity, imagination, and independent ways of action.